THE EFFECT OF E- LIBRARY ON STUDENTS’ ACADEMIC PERFORMANCE IN INDIAN TERTIARY - KIRTI SARASWATI (International Journal of Multidisciplinary Research and Studies, 2021)
The purpose of this study was to investigate the ways in which academic libraries are used by students and to determine whether or not such usage is related to the success that students experience in their academic endeavours. In addition, the investigation sought to determine whether or not such usage is related to the success that students experience in their academic endeavours. Without the library as an integral part of the curriculum, any educational system might be considered insufficient and lacking. It is a very significant factor that has contributed to the improvement of the academic performance as a whole. According to Andaleeb and Simmonds (1998), the use of academic libraries is mostly influenced by the users' awareness of the library's resources and the availability of such resources. This is because users are more likely to utilise resources that they are aware of. It is vital, in order to fulfil the information requirements of students in an efficient manner, to not only have an understanding of the types of material that students need, but also of the ways in which students use the library. The contributions offered by the academic library to the learning process are very helpful and make a major difference. According to the results of Chamani Gunasekera's (2010) study on the student use of an academic library, students are, for the most part, satisfied with the contents, services, and facilities that are made available to them by the library.